High Neutrophil-To-Lymphocyte Ratio Is an Independent Risk Factor for End Stage Renal Diseases in IgA Nephropathy - Wang, Siqing; Dong, Lingqiu; Pei, Gaiqin; Jiang, Zheng; Qin, Aiya; Tan, Jiaxing; Tang, Yi; Qin, Wei (Frontiers in Immunology, 2021)
Background: Complex factors are involved in the development and progression of immunoglobulin A nephropathy (IgAN), a common primary glomerulonephritis worldwide. Autoimmunity and inflammation have been considered to be the basic mechanisms; however, the exact pathogenesis remains unclear. As a novel marker of inflammation, the neutrophil-to-lymphocyte ratio (NLR) has been studied in various diseases. Whether the NLR can predict the renal outcome of patients with IgAN remains unclear. We evaluated the relationships between the NLR and renal function, pathologic lesions, renal progression, and prognosis in patients with IgAN. Methods: This retrospective study involved 966 patients with biopsy-proven IgAN. They were divided into two groups based on the cut-off value of the NLR: the high group (NLR ≥ 2.67, n = 384) and the low group (NLR < 2.67, n = 582). The endpoint was end-stage renal disease. A correlation test was conducted to explore the relationship between the NLR and other important parameter. Kaplan–Meier and Cox proportional hazards analyses were performed to evaluate renal progression and prognosis. Results: The NLR had the highest AUROC, which was 0.633 (p < 0.001). The correlation test revealed that the NLR was positively correlated with serum creatinine (r = 0.127, p < 0.001) and 24-hour urine protein (r = 0.18, p < 0.001) and negatively correlated with eGFR (r = 0.14, p < 0.001). Patients with IgAN who had a high NLR were more likely to have hypertension (p = 0.003). Multivariate Cox regression analysis indicated that a high NLR was an independent risk factor for IgAN even after adjustment for important clinical and pathological parameters (p = 0.043, HR = 1.74, 95%CI: 1.02-2.97). Kaplan–Meier analysis showed that a high NLR was significantly associated with the renal prognosis of patients with IgAN (p < 0.001), especially patients with stage 3 to 4 chronic kidney disease (p = 0.028) or 24-hour urine protein of >1 g/day (p < 0.001). Conclusion: An elevated NLR affects the renal progression and prognosis in patients with IgAN and could be a marker for evaluation of renal function and pathologic lesions.